Physical properties and structural studies of ZnO-PbO-B203 glasses / Norhamiezah Imbaran - Imbaran, Norhamiezah (2014)
Glass samples of compositions 80B2O3 • xZnO • (20-x)PbO with x = 2, 4, 6, 8 and 10 mol% have been prepared by using melt-quenched techniques. Their physical and structural study had been carried out by mean of their density, molar volume, X-ray diffraction as well as FTIR spectroscopy. From the results, the densities are found to decrease from 4.20 g/cm3 to 3.78 g/cm3 with an increase in the ZnO content. Meanwhile, the molar volume is found increases from 21.73 cm3/moI to 22.16 cm3/moI as the ZnO content increased from 2 mol% to 4 mol%. However an addition of ZnO from 4 moI% to 10 mol%, the molar volume start to decreases from 22.16 cm3fmol to 21.14 cm3/moI. Amorphous nature of the glass was confirmed by XRD patterns as they show no sharp peaks as observed. The structural changes with respect to mol% of ZnO content have been studied by FTIR spectroscopy. From the results, there are seven peaks that corresponding to stretching and bending vibrational spectra of borate-based glass functional group.